Case Study on Cyber Crime by Performing Forensic Examination on Social Networking Sites: Exploring the Growing Threat of Cyber Crime on Social Networking Sites (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Crimes in this digital world are of various sorts and the one among is Cyber-crime. As everything is digitized, there is fast increment being used of internet and in the meantime increasingly number of cyber-crimes happens that raised by the aggressors. A portion of the cyber-assaults are hacking, banking frauds, and email spamming and so forth. So as to research these fraudulent exercises, the examination organizations (requirement law) should utilize innovation which is a critical part Also the Mobile gadgets are progressively used to get to social media and texting services, which enable users to speak with others effectively and rapidly. In any case, the abuse of social media and texting services encouraged directing various cybercrimes, for example, cyber stalking, cyber bullying, slander spreading and sexual harassment. In this manner, cell phones are a significant evidentiary piece in digital examination. The principle point of this paper is to display an overview of the developing cybercrime issue and surveys the burdens of over employments of social networking sites. This paper additionally classes a few kinds of cybercrimes that may cause exploitation by these social networking sites. It incorporates few case studies indicating how the individual data is stolen if somebody's profile is as of now enrolled on any social networking sites for either monetary addition or antihuman exercises like illegal tax avoidance and terrorist action separately.